Upaya Peningkatan Prestasi Belajar Mata Pelajaran PKN Melalui Model Pembelajaran Make A Match Pada Materi Norma Masyarakat - Ustadzah Ustadzah (CV. Syntax Corporation Indonesia, 2021)
The scope of the discussion in this study was treated in class VII D of SMP Negeri 17 Surakarta. With a focus on the problem